External Conflict Faced by the Minor Character in “The Martian” Movie - Kadek Dwi Darmawan Sutrisna Putra; I Gusti Ayu Vina Widiadnya Putri; Ida Bagus Gede Nova Winarta (Journal of Language and Applied Linguistics, 2024)
This study focus on the external conflict the minor character faces in “The Martian” movie. External conflict occurs between the character and something outside of himself. External conflicts are divided into three: a conflict between a man, a conflict between man and society, and a conflict between man and nature. This study aims to find out what external conflict the minor character face in the movie faces and how they resolve the conflict. The data for this study were taken from the movie "The Martian" and the screenplay using note-taking techniques. The data were analyzed using qualitative research methods. The theory used is from Kenney (1966:19) and Rahim (2002:81-84). Based on the analysis, found man against man happens mostly in the movie. Further, for handling conflict the main character found mostly is dominating, from 5 types of conflict management: Integrating, obliging, dominating, avoiding, and compromising.